Physical Basics of Semiconductors (Texas Journal of Engineering and Technology, 2023)
The article outlines the fundamentals of materials science and semiconductor technology, which allow one to gain a general understanding of the basic laws of formation of semiconductor phases, the mechanisms of their growth, production conditions, as well as to gain an understanding of the most widely used industrial methods for the production of bulk semiconductors and epitaxial semiconductor films with specified properties. This knowledge is necessary for students specializing in semiconductor physics to understand the specialized literature. Indeed, almost every article devoted to the study of the properties of semiconductors or the creation of devices based on them begins with a description of the method for producing the material, since its properties, as will be shown in this course, are closely related to the method of its production.